2020
DOI: 10.3390/w12071989
|View full text |Cite
|
Sign up to set email alerts
|

On the Occurrence of Metadiaptomus chevreuxi (Calanoida, Diaptomidae, Paradiaptominae) in the Iberian Peninsula, With Notes on the Ecology and Distribution of its European Populations

Abstract: Temporary ponds are one of the most peculiar ecosystems in the world, being characterized by an extraordinarily rich crustacean fauna, with a high degree of endemism. Among them, diaptomid copepods are among the most biogeographically interesting taxa. However, the present knowledge on diaptomid distribution is still far from being exhaustive, even in the relatively well-studied western European countries. In this study, we report the first record of the diaptomid calanoid copepod Metadiaptomus chevreuxi for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…SIC. The species is reported for two temporary water bodies on Favignana island, Sicily (Marrone and Naselli-Flores, 2005;Marrone et al, 2020). Other references : Stoch, 2006a;Marrone, 2006;Marrone et al, 2006aMarrone et al, , 2006bMarrone et al, , 2009Marrone et al, , 2017Belmonte, 2018.…”
Section: Eudiaptomus Vulgarismentioning
confidence: 99%
“…SIC. The species is reported for two temporary water bodies on Favignana island, Sicily (Marrone and Naselli-Flores, 2005;Marrone et al, 2020). Other references : Stoch, 2006a;Marrone, 2006;Marrone et al, 2006aMarrone et al, , 2006bMarrone et al, , 2009Marrone et al, , 2017Belmonte, 2018.…”
Section: Eudiaptomus Vulgarismentioning
confidence: 99%
“…A similar pattern has been observed in the copepod Diaptomus chevreuxi, which also colonizes temporary pools and has separated clades in the south of the Iberian Peninsula, Sicily and Tunisia. This distribution suggests the possible role of migratory birds in north-south dispersal (Marrone et al 2020). In this sense, the arrival of L. jebalae to the Iberian Peninsula is possible by passerine birds during their annual migrations (Viana et al, 2016), taking into account the distance at which it has been found (102 km) with respect to the place where the species has been described (Boix et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…in Sardinia (Becker & al. 2021), and maybe some crustaceans follow the same pattern (Jaume 1989;Marrone & al. 2020).…”
Section: Willdenowia 52 -2022mentioning
confidence: 90%